Criminology a very short introduction - Newburn, Tim (Very short introductions, 2018)
"What do we mean by the term "crime"? Who commits crime and why do they do it? And what can we do about it? This [book] considers what we know about crime and criminality, and about historical trends and competing explanations for patterns of crime in the developed world."...Book flap